Measuring the modulation transfer function of an imaging spectrometer with rooflines of opportunity - Nugent, Paul W; Shaw, Joseph A; Kehoe, Michael R; Smith, Casey W; Moon, Thomas S; Swanson, Rand C (Optical Engineering, 2010)
Measuring the modulation transfer function (MTF) of digital imagers focused at or near infinity in laboratory or field settings presents difficulties because the optical path is longer than a typical laboratory. Also, digital imagers can be hindered by low-resolution detectors, resulting in the resolution of the optics surpassing that of the detector. We measure the MTF for a short-wave infrared hyperspectral imager developed by Resonon, Inc., of Bozeman, Montana, which exhibits both characteristics. These difficulties are overcome with a technique that uses images of building rooflines in an oversampled, tilted knife-edge-based MTF measurement. The dark rooftops backlit by a uniformly cloudy sky provide the high-contrast edges required to perform knife-edge MTF measurements. The MTF response is measured at five wavelengths across the imager's spectral band: 1085, 1178, 1292, 1548, and 1629 nm. The MTF also is observed at various distances from the roof to investigate performance change with distance. Optimum imaging is observed at a distance of 150 m, potentially a result of imperfect infinity focus and atmospheric turbulence. In a laboratory validation of the MTF algorithm using a monochrome visible imager, the roofline MTF results are similar to results from point-source and sine-card MTF measurements.